Assessment of Breastfeeding Knowledge among Mothers in Erbil City - AL-Azzawi, Dr. Sawsan I.I.; Hussin, Dr. kareema A.; Shaker, Dr. Norhan Z. (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background: Breast-feeding is a very natural and normal way designed by God. Breastfeeding is feeding child human breast milk which is preferred for all infants. Although lactation is an automatic physiological process, breastfeeding is a learned behavior that is most successful in supportive environment. This study aimed to assess knowledge of mothers concerning infant and young child breastfeeding, and to use the results as baseline for nutritional intervention programs in the future. Subjects and Methods: A study carried out by interviewing mother at Primary Health Centers to assess mothers breastfeeding knowledge regarding breastfeeding initiation, colostrums use ,exclusivity, duration and extraction of breastmilk, and find the relationship between mothers knowledge and educational levels, family type. Results: (17.5 %) of mothers know that first breast feeding have to be initiated during the 1st hour of child life. (40.4%) of mothers don’t know the importance of colostrums for newborn. (41.1%) of mothers don’t know that child needs 6 months of exclusive breastfeeding. (46.8 %) of mothers don’t agree on breast milk extraction while (35.7%) of them don’t know that breast-milk can be expressed. There was relation between mother knowledge age and education level. Conclusion: mothers have weak knowledge regarding early breastfeeding initiation and exclusive breastfeeding, so breastfeeding promotion, protection and support by health professions necessary for mothers in Erbil.